Development of methodologies for the isolation and culture of cassava immature pollen and zygotic embryos - Cataño C, ML; Mornan, K; Plazas, J; Roca, W. (International Center for Tropical Agriculture, 1993)
Highly efficient systems for the isolation and in vitro culture of cassava pollen and zygotic embryos have been developed. These methodologies have allowed the manipulation of large quantities of isolated pollen from immature and mature anthers for use in studies towards haploid induction and pollen cryopreservation. Conditions were also developed for the isolation, in vitro culture and germination of cassava immature zygotic embryos. The technique was used to recover interspecific Manihot hybrid populations for use in the construction of a cassava molecular linkage map. Culture media and conditions for isolation and culture of pollen and zygotic embryos, and results of work carried out towards the induction of haploidy, will be presented.